A Data-Driven Supply Chain: Marketing Data Sharing, Data Security, and Digital Technology Adoption to Predict Firm’s Resilience - Yudi Fernando; Ridho Bramulya Ikhsan (Binus Business Review, 2023)
Business automation has been driven recently with Technology 4.0 to manage the supply chain process and complexity. The secured data-driven supply chain is critical for business competitiveness. However, not all companies can manage, analyze, and interpret structured and unstructured data wisely. For record-keeping purposes, data are left unprotected and stored. Ideally, it should play a strategic role in decision-making and escalating business performance. The practices are inconsistent with the awareness of data security governance and proper usage of digital technologies. The research aimed to examine the data-driven supply chain that conceptualised marketing data sharing, data security, and digital technology adoption to predict a firm’s resilience. The research applied a quantitative approach. The survey was conducted on Malaysian manufacturing firms. The data were collected electronically and analysed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) 4.0. Around 375 companies participated in the survey. The results show the positive path links from predictors (marketing data sharing, digital technology adoption, and data security governance) and criteria. It also finds that data security and marketing data sharing have impacted digital technology adoption, leading to the supply chain’s resilience. The research has concluded that the secure sharing of the data-driven supply chain can improve a firm’s resilience. Manufacturing companies should make swift focus on data quality and utilize it wisely. The research concludes that empowering data analytics to understand customer preferences is necessary.